Влияние качества медицинской помощи на формирование рынка медицинских услуг в украине - Надюк, Зиновий Александрович (MITEL, 2006)
W artykule analizowana jest współczesna kondycja rynku usług medycznych na Ukrainie. Poziom wiedzy ekonomicznej liderów placówek medycznych ochrony zdrowia jest badany. Na Ukrainie wyznaczane są możliwe drogi rozwoju rynku medycznego.

In the article the modern market condition of medical services is analyzed in Ukraine. The level of economic knowledge of leaders of medical establishments of health protection is studied. The possible ways of medical market development are set in Ukraine.
Wpływ jakości opieki medycznej na kształtowanie się rynku usług medycznych na Ukrainie
Influence of Medical Care Quality on Forming of Market of Medical Services in Ukraine